Demographic Profile of Deaths Due to Drowning in and Around Vijayawada, Andhra Pradesh - K. Ravimuni; K. Usha Rani (Indian Journal of Forensic Medicine & Toxicology, 2022)
Drowning is a leading and preventable cause of death that has suffered an attention deficit. The WorldHealth Organization identifies data collection as a key strategy underpinning effective interventions.The circumstances leading to drowning are complex. People interact with water primarily for recreationand often interact with water due to daily life or occupational endeavours. A Significant reductionthe number of drowning deaths among young children in private swimming pools has been achievedthrough over 30 years of focused work on the epidemiology and risk factors for drowning in privateswimming pools among young children. Proposed contributory factors for drowning in rivers includea lack of barriers controlling access to water, an absence of adult supervision for young children, poorswimming skills, minimal awareness of the dangers, the consumption of alcohol, transportation onwater, a lack of safe water supply, and disasters related to flooding.